2021
DOI: 10.1177/00307270211054211
|View full text |Cite
|
Sign up to set email alerts
|

Why farmers use so many different maize varieties in West Kenya

Abstract: In this article we reflect on the discussions as to whether breeding and seed system development should proceed along its current well established route of developing varieties with a higher agricultural productivity or if the diversity of farmers, their contexts and rationales requires broader approaches. We make use of data from a recently held survey (2018) in West Kenya. The data show that some 80% of the households in the survey planted both local and hybrid maize varieties. The choices that people make a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Therefore, moisture deficiency is reduced, and the plant attains the maximum possible kernels per ear (Walne & Reddy, 2022). The benefits of early sowing dates on crop growth and yields have been confirmed by other studies conducted in western Kenya (Almekinders et al, 2021). Crop modelling applications in the African continent also revealed that production is highly dependent on planting windows (Chisanga et al, 2019;MacCarthy et al, 2018;Tofa et al, 2020).…”
Section: Simulation Of Agricultural Management Strategiesmentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, moisture deficiency is reduced, and the plant attains the maximum possible kernels per ear (Walne & Reddy, 2022). The benefits of early sowing dates on crop growth and yields have been confirmed by other studies conducted in western Kenya (Almekinders et al, 2021). Crop modelling applications in the African continent also revealed that production is highly dependent on planting windows (Chisanga et al, 2019;MacCarthy et al, 2018;Tofa et al, 2020).…”
Section: Simulation Of Agricultural Management Strategiesmentioning
confidence: 76%
“…The cultivar is relatively new, with a yield potential between 9.5 and 15 tonnes per hectare, out-performing other cultivars that have been in existence (Wamalwa, 2013). H614 is one of the oldest cultivars and is popular among farmers, especially in high-altitude regions (Almekinders et al, 2021). According to Obunyali et al, (2019), new cultivars are slowly being adopted due to a lack of performance data under farmers' conditions.…”
Section: Simulation Of Agricultural Management Strategiesmentioning
confidence: 99%
“…Smallholder farmers have many other objectives that are non-farming related based on which they might prefer to spend their available cash (Mausch et al 2021;Verkaart et al 2018). Being cash-constrained is a general phenomenon in West Kenya and even more so for the poorest households (Almekinders et al 2021). Using farmsaved seed that yields sufficiently might therefore be preferred over seed that requires cash but might provide a higher yield.…”
Section: Attributes Used By Farmers To Evaluate Potato Seed Tubersmentioning
confidence: 99%
“…There are reported instances where farmers do not read or understand the safety information displayed on pesticide product labels (Waichman et al 2007). Almekinders et al (2021) also reported the lacking attention of farmers for the information on bags and labels of maize seed in western Kenya. Because in rural Africa, labels do not exist for the majority of the products available, consumers/users find their quality cues in a different way.…”
Section: The Importance Of Certified Seedmentioning
confidence: 99%
“…According to Almekinders et al (2021), in West Kenya, factors that guide the use of local but also improved maize varieties in farmers' fields include for instance rainfall, the availability of cash, the promise of a good yield, the presence of projects and programs, and the culture of seed. By taking into account the socioeconomic and cultural context together with the agroclimatic conditions, the need to use on-farm and ex-situ genetic resource of maize become obvious.…”
Section: Diversity Of Maize Varieties and Implications For Maize Gene...mentioning
confidence: 99%